Enhanced ferroelectricity for nanoporous barium titanate: a phase-field prediction. (2nd September 2021) - Xie, Chengmin; Zhao, He; Du, Lifei; Du, Huiling; Wu, Pingping
ABSTRACT: Porous ferroelectric materials show great potential for achieving competitive dielectric/piezoelectric properties with light weight. In this study, a phase-field model was employed to simulate the ferroelectric domain structure evolution of porous barium titanate. It is suggested that the ferroelectric/dielectric/piezoelectric properties are strongly influenced by the porosity level and the size of pores for porous ceramics. It is demonstrated that the ferroelectric switching behaviour, the remnant polarisation, the dielectric constant and the piezoelectric constant are enhanced in nanoporous ferroelectrics with ellipse-shaped pores by introducing mechanisms of symmetry breaking. By providing a means of achieving enhanced properties, nanoporous ferroelectrics with ellipse-shaped pores may have a broad impact on the applications of ferroelectrics and enhance the utility of the materials for selected applications.